(untitled) (Comprehensive Journal of Science, 2026)
During the last century, and in light of the Fourth Industrial Revolution, which transformed the world in several fields such as e-commerce, industry, medicine, and others, we find that artificial intelligence (AI) is a product of this era. Information technology, which we are currently experiencing, has become an integral part of our daily lives through our use of mobile phones, driving cars, and the design and manufacturing of numerous products. It has even reached all fields, including architecture and architectural design. AI can make design decisions based on your descriptions and produce a distinctive design in mere seconds. The number of architects using AI in their work is constantly increasing, indicating the widespread adoption of AI and suggesting that this adoption will continue to grow in the near future. By studying AI, its patterns, its operational procedures, its decision-making processes, and its ability to predict outcomes and developments related to the data and events presented to it, it has become clear that it can play a vital role in most stages of the architectural design process. The research paper aims to draw attention to the importance and necessity of using smart technologies and artificial intelligence in the field of architecture. The research followed the deductive approach, as it came to codify the role of artificial intelligence in reformulating and practicing the stages of the design process, through putting forward a proposed concept of an artificial intelligence system that is considered an assistant to the designer in performing his work, which depends primarily on applying different patterns of artificial intelligence according to their goals and capabilities in practicing the stages of the architectural design process.